DIALOG KOMUNIKASI PEMASARAN SADHARANIKARAN SEBAGAI STRATEGI MENINGKATKAN BRAND AWARENESS DI BALI SILENT RETREAT - Ni Nengah Puji Widiani; I Gusti Ngurah Sudiana; I Nyoman Alit Putrawan (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2025)
This study was conducted to analyze Sadharanikaran communication dialogue as a strategy to enhance brand awareness at Bali Silent Retreat. The paradigm used is constructivist with a qualitative research approach. The theories employed are Kotler & Armstrong's Marketing Mix and the Sadharanikaran Model of Communication, with data analysis using Ethnographic Content Analysis (ECA). Bali Silent Retreat is a recreational and spiritual retreat destination that offers experiences of meditation, reflection, and healing in a serene and natural environment on the island of Bali, Indonesia. Bali Silent Retreat's marketing communication strategy to enhance brand awareness considers four factors: product, place, promotion, and price. In the Sadharanikaran communication model, sahridaya preshaka (the sender) and sahridaya prapaka (the receiver) share rasa (emotion), bhava (a state of calm and good mind and heart), and sandesha (message delivery) using specific methods and involving a feedback process (pratikriya). This process builds Abhivyanjana (expression, interpretation) of the formed thoughts, leading to Rasaswadana, which interprets the message to achieve shared feelings. This directly enhances social engagement and customer retention, thereby increasing brand awareness.